(untitled) (Damascus University Journal for engineering sciences, 2021)
Processing of transferring data spreaded widely with spreading the multi systems which work over the internet like cloud computing and others systems. These systems need to security systems to protect data against steeling, spy and changing and to insurance privacy for users. RSA and AES algorithms considered the main algorithms to design security systems. This research purposes to design model for security data depending on combining RSA and AES in parallel to benefit from the advantages of both algorithm RSA and AES and to get higher security model. The research proposes parallel hybrid algorithm depending on segment file size into sub blocks with 128-bit size and encrypted these blocks by RSA and AES in parallel. Proposed system is designed to give ability to protect data using RSA, AES or proposed hybrid algorithm. Performance of those three algorithms are compared to calculate time of encryption and decryption time for both of them.